TPLF’s annexation of Wolkait, Ethiopia: motivations, strategies, and interests - Alene Kassaw; Mbabazi Veneranda (Cogent Social Sciences)
Ethiopia has been riddled with conflicts of varying nature and magnitude, some of which have threatened its very survival. It was to stem this scourge of conflicts that ethnic-based federalism was adopted in 1991. Sadly, the federal dispensation has not worked well in terms of preventing conflicts as various forms of local conflicts engulfed most parts of the country. In the existing sources, these conflicts are often characterized as ‘ethnic’, despite the real issues being resources, territory, power, etc. The article investigated the conflict in Wolkait, one of the conflict hotspots since 1975. The findings gleaned from pertinent data, both primary and secondary, show that the conflict has its roots in the formation of the TPLF in 1975 with its ‘Greater Tigray Manifesto’. As stated in its manifesto, the TPLF sought to establish an independent ‘Republic of Greater Tigray’ by annexing territories from Amhara (Wolkait and Telemt from Gondar and Raya from Wollo), and Eritrea’s port of Assab. Upon state power capture in 1991, the TPLF championed ethnic federalism as a politico-legal strategy to redraw the previous administrative boundaries and legitimize the annexation of Wolkait, Telemt, and Raya. Annexation of Wolkait outside of any constitutional-legal framework was meant to help the TPLF further political and economic motives: vengeance against the Amhara, a springboard for further territorial annexations, a site of resettlement of Tigrayans, and a foundation for the establishment of ‘The Republic of Greater Tigray’.